Immunohematological features of free-living Alouatta belzebul (Linnaeus, 1766) red-handed howler monkeys in the Eastern Amazon - Guimarães, Victor Yunes [UNESP]; Zanoni, Diogo Sousa [UNESP]; Alves, Carlos Eduardo Fonseca; Amorim, Reneé Laufer [UNESP]; Takahira, Regina Kiomi [UNESP] (Springer Nature, 2022)
The red-handed howler monkey (Alouatta belzebul) is one of the 35 threatened Brazilian primate species found in two highly endangered Brazilian biomes. Their Amazonian native populations have been declining due to exponential deforestation associated with human activities, especially the construction of dams. The studied population (n = 27) was located in the Belo Monte dam Area of Influence. For the first time, we presented hematological parameters and the basic profile of T (CD3) and B (BSAP PAX5) cells by immunocytochemistry. The results supported the hypothesis that the immuno-hematological profile is influenced by sex, age, and season. Eosinophils were significantly higher in females (p = 0.03), monocytes statistically greater in juveniles (p = 0.04), and total plasma protein increased significantly (p > 0.001) during the dry season. Furthermore, adults showed a statistically higher average absolute number of B lymphocytes than young individuals (p = 0.03), in contrast to T lymphocytes. Even without knowing the full history of antigenic exposure, these results not only contribute to elucidating the boundaries between health and disease but may help lay the groundwork for future research into the effects of anthropogenic stress on immune activation.
Keywords: Complete blood count; Immunocytochemistry; Lymphocyte subset; Neotropical primate